2021
DOI: 10.1016/j.bpsc.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Higher Executive Control Network Coherence Buffers Against Puberty-Related Increases in Internalizing Symptoms During the COVID-19 Pandemic

Abstract: Background Early pubertal maturation has been posited to be a biopsychosocial risk factor for the onset of internalizing psychopathology in adolescence; further, early-maturing youth exhibit heightened reactivity to stressful events. School closures and enforced social distancing, as well as health and financial uncertainties, during the COVID-19 pandemic are expected to adversely affect mental health in youth, particularly adolescents who are already at risk for experiencing emotional difficultie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 86 publications
6
58
0
Order By: Relevance
“…For instance, schools transitioning from in-person to remote may have affected meal access, academic instruction, social interaction, and mental health services ( Golberstein, Wen, & Miller, 2020 ; Guessoum et al, 2020 ). Indeed, the impact of COVID-related stress has been observed in adolescents who exhibit elevated internalizing symptoms during the pandemic compared to the three months prior ( Chahal et al, 2020 ) and compared to younger youth ( Tang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, schools transitioning from in-person to remote may have affected meal access, academic instruction, social interaction, and mental health services ( Golberstein, Wen, & Miller, 2020 ; Guessoum et al, 2020 ). Indeed, the impact of COVID-related stress has been observed in adolescents who exhibit elevated internalizing symptoms during the pandemic compared to the three months prior ( Chahal et al, 2020 ) and compared to younger youth ( Tang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pubertal stage was estimated using the self-reported Tanner Staging Questionnaire ( Morris and Udry, 1980 ), which is significantly correlated with physician ratings of puberty-related physical development ( Shirtcliff et al, 2009 ). We averaged the Tanner pubic hair and breast/testes ratings to compute an index of overall pubertal development ( Dorn et al, 2006 ), as done previously in this sample ( Chahal et al, 2020a , 2020b ).…”
Section: Methodsmentioning
confidence: 99%
“…We used Fixel-based Analysis (FBA) to assess the morphometry of WM tracts, as done previously in this sample ( Chahal et al, 2020a , 2020b ). Briefly, we applied higher-order diffusion models to fiber populations within each voxel (i.e., fixels) in order to estimate a combined measure of fiber density and cross-section (FDC).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, depressive symptoms in adolescents appear to be increasing during this period (6,7). It is almost certain that some adolescents are more vulnerable than others to experiencing difficulties during the COVID-19 pandemic, differences that have been found to be indexed by neurobiological and physiological markers (8)(9)(10). We recently showed that aspects of neurobiology can moderate risk and resilience to depressive symptoms during the COVID-19 pandemic (8,10), and, therefore, might serve as targets for intervention and prevention.…”
mentioning
confidence: 99%
“…It is almost certain that some adolescents are more vulnerable than others to experiencing difficulties during the COVID-19 pandemic, differences that have been found to be indexed by neurobiological and physiological markers (8)(9)(10). We recently showed that aspects of neurobiology can moderate risk and resilience to depressive symptoms during the COVID-19 pandemic (8,10), and, therefore, might serve as targets for intervention and prevention. Moreover, identifying developmental factors that are associated with predictive markers of mental health during the COVID-19 pandemic could inform efforts to promote resilience to psychopathology during future periods of stress.…”
mentioning
confidence: 99%